Deuda de la documentación en el desarrollo ágil de software: mapeo sistemático de la literatura - Narváez-Narváez, Juan-Carlos; Pardo-Calvache, César-Jesús; Orozco-Garcés, Carlos-Eduardo (Revista Científica, 2023)
In software development, documentation is a continuous process that specifies what the system does, how it does it, and for whom it does it, describing all its characteristics from different perspectives in order to facilitate the understanding of all the interested parties. However, this is not always achieved due to poor documentation practices, leading to a type of technical debt known as documentation debt, which is related to missing, inconsistent, or incomplete documentation that degrades the understanding of the system, severely affecting its development, maintenance, and evolution. This phenomenon seems to be aggravated in agile approaches, either due to a misunderstanding of agile values ​​and principles by focusing on the continuous delivery of functional software rather than comprehensive documentation, or a lack of good documentation practices. Although there are initiatives that generally describe the causes, effects, and good practices to mitigate documentation debt, it is still necessary to understand the impact of this type of debt on the software industry and to delve into a more complete definition in agile software development. In this sense, the results of a systematic mapping are presented, which provide a solid base of knowledge about documentation debt in agile software development and allow identifying gaps or research opportunities in this topic.